Revitalisasi Peran Komite Dalam Meningkatkan Mutu Pendidikan di Sekolah - Ridhwan M Daud (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The School Committee is an independent institution comprised of parents/guardians of students, the school community, community leaders, and education experts who are committed to education. This article outlines the importance of revitalizing the role and contribution that the School Committee must provide in improving the quality of education. The School Committee serves as a bridge between the school and the community, and how their involvement can help achieve better educational goals is discussed. Through comprehensive analysis, this article highlights the importance of the School Committee's involvement in formulating policies, suring transparency, and raising funds for education. Additionally, indicators of the School Committee's involvement in improving the quality of education are presented, including aspects of education quality and relevance, equalization and expansion of education, and educational management. The School Committee can be a platform capable of bringing about significant changes in the education system, and it provides a clear view of how the success of schools can be evaluated according to national education standards. The involvement of the School Committee is considered as a factor in efforts to realize quality education services for all students.